Analisis Usaha Pengolahan Ampas Ubi Kayu (Gepe) di Desa Waai Kecamatan Salahutu Kabupaten Maluku Tengah - Ester D. Leatemia; Natelda R. Timisela; Febby J. Polnaya; Rachel Breemer (Universitas Pattimura, 2016)
The purposes of this study were to find out the characteristics of cassava dregs (gepe) agroindustry and to analyze the feasibility of cassava dregs (gepe) agroindustry in Waai Village. The method used was case study method towards cassava dregs (gepe) agroindustry businessmen as many as 50 respondents. Data collected in this study were primary data and secondary data. Data obtained then were analyzed by using qualitative and quantitative analysis. Descriptive analysis was used to answer the first objective about the characteristics of cassava dregs (gepe) agroindustry. The B/C analysis was used to answer the second objective about the feasibility of cassava dregs (gepe) agroindustry. The results showed that the characteristics of cassava dregs (gepe) agroindustry were: 1) the raw materials for gepe agroindustry in Waai village was cassavas. Cassavas used as raw materials in Waai village were edible cassavas and poisonous cassavas with high HCN content; 2) The processing of gepe in Waai Village used semi-mechanical technologies such as jack and grated machine; 3) Production cost for the processing of gepe was an average of Rp. 3,181,066 per month; 4) The production of gepe in Waai Village was an average 41.06 kg per month; and 5) The marketing of gepe was through two distribution channels, that respondents sold to village wholesalers in Waai village with the selling price ranging from Rp. 4,735/kg to Rp. 4,912/kg and sold directly to consumers in Batu Merah Traditional Market with the selling price of Rp. 5,263/kg. The cassava dregs agroindustry in Waai Village was feasible because the B/C ratio is 2.50 which is greater than 1.